Impaired Mitophagy of Nucleated Erythroid Cells Leads to Anemia in Patients with Myelodysplastic Syndromes. (3rd June 2018) - Jiang, Huijuan; Yang, Liyan; Guo, Lifang; Cui, Ningbo; Zhang, Gaochao; Liu, Chunyan; Xing, Limin; Shao, Zonghong; Wang, Huaquan
Abstract : Myelodysplastic syndromes (MDS) are a heterogeneous group of clonal stem cell disorders characterized by cytopenia and dysplasia. Anemia is the most common symptom in patients with MDS. Mitophagy and mitochondrial dysfunction might be involved in the development of MDS. In this study, we investigated the change of mitophagy in erythroid precursors in MDS patients. We found that NIX-mediated mitophagy was impaired in bone marrow nucleated red blood cells (NRBC) of MDS patients, associated with an increased amount of damaged mitochondria and increased ROS level which might lead to apoptosis and ineffective erythropoiesis. The results showed that the amount of mitochondria in GlycoA + NRBC positively correlated with the count of ring sideroblasts in bone marrow samples. Meanwhile, the level of autophagy-associated marker LC3B in GlycoA + NRBC had a positive correlation with hemoglobin (Hb) levels, and the amount of mitochondria in GlycoA + NRBC had a negative correlation with Hb levels in high-risk MDS patients. Our results indicated that mitophagy might involve the pathogenesis of anemia associated with MDS. Autophagy might be a novel target in treatments of MDS patients.